Antimicrobial Activity of Pecut Kuda Leaf Extract (Stachytarpheta jamaicensis (L. Vahl) against Mycobacterium smegmatis - Putri Nadia Ramadhani; Ika Dyah Kurniati; Maya Dian Rakhmawatie (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2023)
Mycobacterium smegmatis infrequently causes infection, but it is easy to be pathogenic in immunosuppressed patients. Many reported that M. smegmatis resistance to several antibiotics became an impetus for searching for new antimicrobials. Therefore, this study aims to prove the effect of Pecut Kuda leaf extract (Stachytarpheta jamaicensis (L.) Vahl) on the growth of M. smegmatis mc2 155. This research is an experimental study with a post-test control group design. The susceptibility test was carried out using the two-fold microdilution method and resazurin staining. The concentration of Pecut Kuda leaf ethanol extract was prepared in the concentration range of 10000.0 – 625.0 µg/ml.  Phytochemical analysis of the content of saponins, tannins, flavonoids, and alkaloids was also carried out on Pecut Kuda leaf ethanol extract. Pecut Kuda leaf ethanol extract can inhibit the growth of M. smegmatis with a minimum inhibitory concentration (MIC) of 5000 µg/ml (very weak activity) because, at the highest concentration of 10000 µg/ml, M. smegmatis still cannot be killed. Furthermore, Pecut Kuda leaf ethanol extract contains saponins, tannins, flavonoids, and alkaloids which are known to have antibacterial activity. However, further evaluation is needed to maximize the antibacterial activity of Pecut Kuda leaf extract, for example, by fractionating the extract.